Museum receives donation (Raton, NM Raton Range, 1977)
This article is about the Raton Historical Museum receiving its first donation.
Newspaper article
Master list item #: 86
File location is in the Raton file Cabinet
Keywords: Short, Betty -- Folsom Museum President; DiLisio, Joe Sr; Kastler, Joe; Southwell; Reese, Rick; Raton Historical Museum; Folsom Museum; Palace; Donations; Museum Business; Museum Exhibits; Raton, New Mexico